Chapter 8 'Balancing human needs with technology'-a design-led approach for exploring an earthquake early warning system in Aotearoa New Zealand - Tan, Marion Lara (Taylor & Francis, 2024)
Earthquake early warning (EEW) for Aotearoa New Zealand is in its infancy. Establishing a public EEW system in New Zealand that can warn the general population comes with several reservations as there are many technological, societal, and cultural challenges to overcome. Even with recent technological advances, a successful EEW system will rely on people to react appropriately to the alerts and follow protective action recommendations, such as Drop, Cover, and Hold. Designing an EEW system requires a multidisciplinary approach that involves multiple stakeholders, including the public. This chapter introduces an overarching design science approach in investigating the feasibility of an EEW solution for New Zealand. It includes a participatory design method used for eight community workshops to understand people's views on EEW. The workshop participants envisaged an EEW system for New Zealand that considers the intersections between services and technology, communication, and human behavior. They expected a holistic EEW system to incorporate public engagement, transparency, and inclusion. The design-led approach described in this chapter puts people at the center, encouraging a close engagement with communities to inform the development of relevant and trusted technological solutions. The robust engagement processes provide insights relevant to designing an EEW system for New Zealand.